2012
DOI: 10.2169/internalmedicine.51.6775
|View full text |Cite
|
Sign up to set email alerts
|

An Elderly Patient with Diabetic Nephropathy Complicated by ANCA-associated Nephritis

Abstract: A 67-year-old man, on oral therapy for type 2 diabetes mellitus since 1990, had sustained proteinuria since 2005. When hematuria was first discovered in 2008, renal dysfunction [creatinine (Cr), 1.2 mg/dL], inflammation [C-reactive protein (CRP), 12 mg/dL] and high myeloperoxidase anti-neutrophil cytoplasmic antibodies (MPO-ANCA) levels [546 ELISA units (EU)] were observed. Renal biopsy showed the diagnosis of ANCA-associated nephritis combined with diabetic nephropathy. For this patient, there was pathologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The patient in our case had diabetes for more than 30 years. To date, there have been only 10 reported cases of diabetic nephropathy with antineutrophil cytoplasmic antibodies mediated nephritis 12. Of the 10 cases, only three cases showed the pathological evidence of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The patient in our case had diabetes for more than 30 years. To date, there have been only 10 reported cases of diabetic nephropathy with antineutrophil cytoplasmic antibodies mediated nephritis 12. Of the 10 cases, only three cases showed the pathological evidence of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include the human leucocyte antigen-DR4 genotype, female sex, slow hepatic acetylators, and in patients with a history of thyroid disease. 3,4…”
Section: Discussionmentioning
confidence: 99%
“…Other risk factors include the human leucocyte antigen-DR4 genotype, female sex, slow hepatic acetylators, and in patients with a history of thyroid disease. 3,4 The pathogenesis of hydralazine induced vasculitis is not well-understood. It possibly has multifactorial involvement.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the increased proteinuria may be due to the synergetic effects of the multiple coexisting diseases. [10][11][12] Even though massive proteinuria is usually the initial disorder in nephrotic syndrome (NS), the exact pathogenesis of hypoalbuminemia in NS is not clear, because it is not always associated with nephroticrange proteinuria [13]. In their study, Xu et al found that there was no difference in the serum albumin levels of ANCA GN patients with and without nephrotic-range proteinuria, which indicates that proteinuria may not induce hypoalbuminemia in AAV.…”
Section: Figure 6: Gram Stain Showing Crescentic Glomerulonephritismentioning
confidence: 99%